PENGARUH MOTIVASI AUDITOR, TIME BUDGET PRESSURE, DAN KOMPLEKSITAS AUDIT TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI BATAM - Joane Joane; Dian Efriyenti (SCIENTIA JOURNAL, 2026)
Although regulatory reinforcement and auditing standards have been continuously strengthened, they have not fully guaranteed the achievement of optimal audit quality, as reflected in the continued occurrence of financial statement fraud cases, such as that experienced by PT Indofarma Tbk. The determinants of audit quality constitute a broader framework, encompassing not merely regulatory compliance, as well as auditor’s inherent characteristics and the specific contours under which audit engagement are performaned. This investigation seeks to examine how three specific factors (auditor motivation, time budget pressure and audit complexity) collectively impact audit quality conducted within public accounting firms located in Batam. A quantitative methodology was utilized to collect primary data, using structured questionnaires administered to the respondents. A saturated sampling method was applied, resulting in 69 auditor respondents. The t-test results indicate that auditor motivation, time budget pressure and audit complexity have a significant impact on audit quality. Furthermore, the F-test results demonstrate that audit quality is simultaneously determined by all three variables